1998
DOI: 10.1097/00005344-199808000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Treatment with Enalapril in Streptozotocin Diabetic and DOCA Hypertensive Rats

Abstract: We studied the effects of long-term treatment with enalapril (5 mg/kg/day orally) on various biochemical and cardiovascular complications in streptozotocin (STZ) diabetic and deoxycorticosterone acetate (DOCA) hypertensive rats. Female Wistar rats made diabetic or hypertensive or both by streptozotocin (STZ; 45 mg/kg) or deoxycorticosterone acetate (DOCA; 10 mg/kg, p.o., daily) or both. Enalapril (5 mg/kg) was administered daily by the oral route for 6 weeks. At the end of 6 weeks, blood samples were taken to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The vasculature is one of the main locations of the enzyme, where activity of ACE promotes vascular responsiveness and cellular proliferation. 42,43 There is evidence of a higher activity of this enzyme in serum and some tissues such as ventricle and lung 11,12,16 in STZ-induced diabetic rats, but also a reduction of activity has been described in renal tissue. 18 The objective of this study was to study the association of somatic and nACE protein expression and enzymatic activity in the renal tissue homogenate of Wistar rats, in which DM was induced by streptozotocin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vasculature is one of the main locations of the enzyme, where activity of ACE promotes vascular responsiveness and cellular proliferation. 42,43 There is evidence of a higher activity of this enzyme in serum and some tissues such as ventricle and lung 11,12,16 in STZ-induced diabetic rats, but also a reduction of activity has been described in renal tissue. 18 The objective of this study was to study the association of somatic and nACE protein expression and enzymatic activity in the renal tissue homogenate of Wistar rats, in which DM was induced by streptozotocin.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Furthermore, it has been postulated that in diabetes there is a role for the RAS in mediating many of the functional effects such as changes in intraglomerular haemodynamics 9 as well as structural changes in the diabetic kidney at both glomerular and tubulointerstitium levels. 9,10 There is strong evidence that angiotensinconverting enzyme (ACE) activity is increased in serum 5,[11][12][13][14][15] and tissues such as lung, 11,12 ventricle, 16 mesenteric artery, 17 aorta and heart 18 of STZinduced diabetic rats. Insulin treatment could reverse some of these changes, 19 but the mechanism by which insulin treatment affects ACE activity is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Under STZ-induced diabetic conditions, myocardial ACE levels have been found to be unchanged and/or increased, depending on the experimental design (8,9). These inconsistent results may be the consequences of uncontrolled intracellular protein activation of the used homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…Control rats treated with PE were not studied because it has been previously shown that ACEi does not modify EC or skeletal muscle mitochondrial function under basal conditions (Bahi et al 2004). Similarly, although data are controversial concerning the blood pressure, it has been reported that ACE inhibitors do not modify blood glucose or insulin in normal rats (Predel et al 1994;Dal Ponte et al 1998;Goyal et al 1998).…”
Section: Animals and Experimental Designmentioning
confidence: 99%